ANALISIS PERILAKU WORK FROM CAFÉ DALAM MENINGKATKAN CUSTOMER EXPERIENCE MELALUI LINGKUNGAN FISIK - Nur Fadilah Ayu Sandira (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to understand the work from café phenomenon as a contemporary consumption practice by exploring consumer experiences in utilizing café spaces as alternative work environments. This research adopts a qualitative exploratory approach. This study was conducted at Eksposed Signature as a representation of an urban café in Makassar City. Data were collected through in depth interviews, observations, and documentation. The findings reveal that work from café is not merely perceived as an alternative workspace but has evolved into an experiential consumption practice that integrates productivity, comfort, and social interaction. Consumer experience is shaped by the interaction between the café environment, including ambiance, spatial comfort, and layout, and digital support, such as WiFi and power outlets that enable work activities. Furthermore, this activity reflects experiential consumption, where consumers not only utilize the functional aspects of space but also engage with the atmosphere and social dynamics within the café setting. Additionally, positive experiences encourage repeated consumption behavior, including longer visit duration, repeated purchases, and a tendency to revisit the same place. This study contributes to the understanding of work from café as a modern consumption practice influenced by the integration of physical environment and digital support within an urban context.